PERAN KOMUNITAS PEMUDA HIJRAH SEBAGAI KONTROL SOSIAL DI JORONG KOTO ALAM NAGARI PADANG GANTING KECAMATAN PADANG GANTING KABU - Wenny Marlina; Sri Rahmadani; Ariesta . (Turast: Jurnal Penelitian dan Pengabdian, 2021)
The hijrah youth community is a youth organization that has the aim of improving itself in a better direction because the people in that area have behavior that deviates from the values and norms prevailing in society as a result of disturbed community life. Based on this background, the community collaborates with the youth alumni of the Az Zahra Mosque to form a community called the Hijrah youth community which is closely related to religious values whose purpose is to instill religious values in the community while business is to improve the economy of the community. The theory used in this study is the theory of social control according to Hirschi Travis. This research is a qualitative approach with a descriptive type. The results of research on the role of the migrating youth community as social control are: 1) internalization of religious values, namely the transfer of values carried out by the migrating youth community by approaching religious activities, 2) approaching individuals, the approach is carried out by seducing, inviting, being approached, care and pay attention to changes in behavior, 3) holding events as well as introductions, the community also introduces individuals to other individuals through activities, through social media, radio and through international seminars, 4) disseminates values and norms, namely the process of instilling values and norms , the goal is to shape a person's character and 5) carry out positive / beneficial activities, the goal is to prevent deviant behavior for example religious and social activities.